2018
DOI: 10.1039/c7fo01824j
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of major allergens and allergenicity reduction of soybean meal through solid-state fermentation with microorganisms

Abstract: In this study, we determined whether solid-state fermentation could degrade major allergens and reduce potential allergenicity of soybean meal (SBM). Solid-state fermentation was realized through a mixture of Lactobacillus casei, yeast, and Bacillus subtilis. High-performance liquid chromatography, size exclusion-high-performance liquid chromatography, and capillary liquid chromatography/tandem mass spectrometry coupled with electrospray ionization were used to examine the total amino acids and molecular weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(45 citation statements)
references
References 46 publications
2
32
0
Order By: Relevance
“…In addition, total serum IgG and IgE antibody levels were increased in the allergy group, which were similar to the findings from other studies ( Friesen et al, 1993 ; Sun et al, 2009 ; Yang et al, 2018 ). Previous studies have shown that FOS can enhance immunity by increasing total serum IgG in swine ( Apper et al, 2016 ; Wang et al, 2017 ).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, total serum IgG and IgE antibody levels were increased in the allergy group, which were similar to the findings from other studies ( Friesen et al, 1993 ; Sun et al, 2009 ; Yang et al, 2018 ). Previous studies have shown that FOS can enhance immunity by increasing total serum IgG in swine ( Apper et al, 2016 ; Wang et al, 2017 ).…”
Section: Discussionsupporting
confidence: 91%
“…However, various ANFs, such as antigenic protein and trypsin inhibitors, limit its wide application in animal feed [ 26 ]. A growing number of studies indicate that microbial fermentation is an economically and widely available method to solve the issues of SBM [ 2 , 21 , 27 ]. In pig production, extensive evidence has shown that FSBM or fermented feed improves growth performance, nutrient digestibility, and immune function [ 16 , 19 , 26 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…and fermented at 37 °C for 24 h. After the first stage of fermentation, the fermented mixture was transferred to a plastic bag equipped with a one-way valve (Rou Duoduo Biotechnology Co., Beijing, China) and anaerobically incubated at 37 °C for 24 h. After fermentation, the FSBM was dried at 60 °C for 10 h. The crude protein and dry matter of the SBM or FSBM were measured according to AOAC (2005). The content of TCA-SP in the SBM and FSBM was analyzed using (TCA) according to the China National Standard (GB/T 22492-2008) [ 21 ]. The contents of glycinin and β-conglycinin in the SBM and FSBM were tested using competitive enzyme-linked immunosorbent assay (ELISA) kits (Longkefangzhou Bio-Engineering Technology Company, Beijing, China) according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Splenic cell culture was based on the studies by Yang et al . Briefly, each well was inoculated with 2 × 10 6 cells (24‐well plate), and then PBS, SM, and FSM (50 mg/mL) were added to be incubated with splenic cells for 72 h (37 °C and (CO 2 :air = 1:19, v/v)).…”
Section: Methodsmentioning
confidence: 99%